Modelling Crystallization Detection in Single-effect Aqua-LiBr Vapor Absorption Cooling Systems - Salem M. Osta-Omar; Moutaz Elgammi (African Journal of Advanced Pure and Applied Sciences, 2025)
Single-effect aqua-LiBr vapor absorption cooling systems are widely used in cooling applications due to their ability to utilize low-grade energy sources and their environmentally friendly characteristics. However, a significant operational challenge is the risk of crystallization, which occurs when the aqua-LiBr solution reaches its highest concentration and lowest temperature, exceeding the crystallization boundary. This phenomenon is particularly critical at the inlet of the absorber after aqua-LiBr solution leaving the solution heat exchanger, especially under decreasing ambient temperatures. Crystallization can obstruct system components, reduce efficiency, and ultimately lead to system failure. This paper presents a model for detecting crystallization in single-effect aqua-LiBr vapor absorption cooling systems through thermodynamic analysis, enabling the identification of safe operational conditions. Additionally, a correlation equation is provided for determining the minimum critical temperature ( ) of the absorber and condenser, beyond which crystallization occurs. This equation is only validated for desorber temperatures ranging from 60℃ to 120℃ and solution heat exchanger effectiveness values between 0.5 and 0.9, demonstrating a high coefficient of determination (R²).